The Effects of Questioning Strategy in Teaching Simple Poetry in Introduction to English Literature - Antonius Gurito; Agustinus Ngadiman (Magister Scientiae, 2010)
This study aims at determining the effects of questioning strategy in teaching simple poetry in introduction to English literature. A quasi-experimental study applying a pretest-posttest control group design was employed. A sample of 99 students was purposefully selected from the accessible population of S1 students taking Introduction to English Literature at an English Department Surabaya. The experiment was conducted for 16 weeks. Two types of data were collected: the students’ scores of reading comprehension and the types of questions generated by the students. Two types of test, and objective reading comprehension test and a subjective reading comprehension test were administered. The study proved that both provided and generated questions promote reading comprehension better than reading-only. The study also proved that selfquestioning is the most effective strategy for comprehending selections